Strategic Leadership Transformation in Addressing Non-Traditional Security Threats in Indonesia: A Narrative Literature Review - Mayyasari T. Gondokusumo; Asep Adang Supriyadi; Ceppi Hilmansyah; Joni Widjayanto (LPPM STIE KRAKATAU, 2026)
This study examines strategic leadership transformation in addressing non-traditional security threats in Indonesia and develops an adaptive strategic leadership framework by integrating transformational leadership, adaptive leadership, and legitimacy theory. A qualitative narrative literature review was conducted on 56 Scopus- and ScienceDirect-indexed articles (2015–2026). The selected articles were analyzed thematically through data reduction, categorization, and conclusion drawing. The findings show that transformational and adaptive leadership improve defense-organization performance, while non-traditional threats require more flexible leadership approaches. The Indonesian context presents challenges related to civil–military dynamics, defense coordination, cyber threats, disinformation, and public legitimacy. The study concludes that effective transformation requires the integration of leadership capacity, institutional synergy, and social legitimacy to strengthen responses to non-traditional security threats. This study is limited by its reliance on secondary literature from two databases and the absence of primary empirical data, requiring future validation through field studies. This study contributes to leadership and defense studies by contextualizing adaptive strategic leadership in Indonesia and providing practical insights for defense institutions in managing emerging security challenges.